Congestion in Latin American cities: Innovative approaches for a critical issue - Juan Pablo Bocarejo (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper surveys trends in private vehicle use in Latin American cities and related government policies. It discusses the Colombian government's initiatives to adopt congestion charging in major cities, highlights the political constraints encountered, and discusses policy changes adopted in response. The paper presents modelling results for the impact of different congestion charging proposals and identifies the principal challenges for adopting them.
Keywords: 330; Verkehrsstau; Verkehrsverhalten; Kommunale Verkehrspolitik; Stadtverkehr; Lateinamerika